The Impact of Autoimmune Hepatitis and Its Treatment on Health Utility. Issue 4 (5th October 2018) - Wong, Lin Lee; Fisher, Holly F; Stocken, Deborah D; Rice, Stephen; Khanna, Amardeep; Heneghan, Michael A; Oo, Ye Htun; Mells, George; Kendrick, Stuart; Dyson, Jessica Katharine; Jones, David E. J.; ,
Abstract : Patient reporting suggests that the physical and psychological effects of autoimmune hepatitis (AIH) can be substantial. However, health‐related quality of life (HRQOL) in patients with AIH remains incompletely characterized, and health utility remains to be explored. Treatment for AIH often includes the use of corticosteroids, which are agents that can be associated with significant adverse effects. Here we explore the impact of AIH and its treatments on patient‐reported HRQOL and health utility in a large cohort of prevalent cases from the United Kingdom Autoimmune Hepatitis (UK‐AIH) national study. Data were collected from 990 adult participants with a clinical diagnosis of AIH using validated HRQOL tools including the European Quality‐of‐Life 5‐Dimension 5‐Level (EQ‐5D‐5L) and clinical data forms. The EQ‐5D‐5L dimension scores were compared with UK population norms and with a disease control cohort with primary biliary cholangitis (PBC). Within the AIH cohort, regression analysis was used to explore associations between HRQOL and demographic and clinical variables with a particular focus on the impact of AIH therapies including corticosteroid use. HRQOL, measured by the EQ‐5D‐5L utility index, is shown to be significantly impaired in our cohort of AIH patients compared with population norms. Within the AIH cohort, corticosteroid use was found to be significantly associated with impaired HRQOL, even when controlling for biochemical disease activity status. Conclusion: Our data show evidence of HRQOL impairment in a large cohort of AIH patients compared with the general population. Furthermore, corticosteroid use is strongly associated with decreased HRQOL, independent of remission status. This highlights the need for better corticosteroid‐free therapy approaches and it emphasizes the need for future novel therapeutic trials in AIH. (Hepatology 2018; 00:000‐000).